Desain dan Implementasi Sistem Pencatatan Pemungutan Suara dengan Teknologi Blockchain pada Jaringan Peer-to-Peer - Rifa Hanifatunnisa; Muhammad Ismail (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Voting is one of the important parts in democratic system, which is mostly done conventionally. The implementation of voting activities managed by one party or organization makes the results of voting results vulnerable to manipulation. Blockchain, as a technology that can secure data, can be used as one solution to overcome fraud in the voting process. Voting result data is recorded in the blockchain, then the data is sent to many parties. This distributed data also depends on one party about the results of the voting data. This study discusses the application of a voice recording system using blockchain technology and the process of distributing the data in a peer-to-peer network. In this system, TPS is a node on the network that will record, sign, and then transfer the data to other nodes that are connected to each other in a peer-to-peer network. That way, the data from the voting results of each node will be stored in all nodes. In addition, the results of the voting can be seen in real-time and the process of counting the results of the voting can be done faster.